Investigation of Behaviors of Concrete Shear Wall in High-Rise Steel Buildings - Mukhlis Ahmad, Hajiyev; Dabbaghasadollahi Poor, Hasan (International Journal of Engineering and Technology, 2018)
This study focuses on an analytical study on reinforced steel structures with concrete shear wall. The structures studied was analyzed using nonlinear time history method and the effect of installingÂ  concrete shear walls in the structural plan on the target point displacement. By comparing the roofs' displacement diagrams in different structures with different layout of the shear wall in the plan, it is concluded that in order to achieve the proper result in the design of the structures, the shear walls must be located in the middle of the plan in form of core and enclosed with structural columns.Â Â